(untitled) (London Journal of Research In Humanities and Social Sciences, 2026)
This paper is aimed to discuss Karl Marx’s works, its flaws and merits, in order to offer a historical comprehension of its content and determinant conditions. Departing from a philosophical and cultural tradition still too much in debt to the classical tradition, it is argued that Marx had never thoroughly accomplished the allegedly inversion of Hegel’s Idealism in his own works. Trying to articulate philosophy of history to the critical study of classical Political Economy, under the dialectical historical materialism theory, Marx lost the final cohesive aspect of his reflections while ideologically promoting ethical-moral values which he had understood to be urgent the diffusion through the industrial Europe at his time. The cultural background Marx was inserted in was still too much charged by religious values, which used to function as guidance principles to human lives and actions towards the future. Here the problem is not strictly about the secularization process of historical teleology or the meaning of history, but about how alienation in both Marx and Hegel may be fundamental to understand and justify the unfolding of human world as the realization of history, either under Reason or historical materialism. The strict Political Economy content of his works shall also be evaluated so we can state the most important part of his overall work relates to the political humanitarian perspective belonging to the superstructure dimension of human affairs, despite not losing its Political Economy intellectual value.